A prática fotográfica como construção simbólica do cotidiano de alunos da rede pública metropolitana de Curitiba - Silva, Regiane Moreira da (2010)
This study aims to discuss the relationship between students at the suburb of Curitiba with imaging technology, and how these images represent the daily lives of these boys and girls. For this, an experiment was performed where teens made the capture of images using pinhole, digital and analog cameras. Using the theoretical questions from Arlindo Machado, Flusser and Nestor Garcia Canclini, we start from the premise that the visual discourse is a dynamic process and is crossed by social, economic, technological, physical and cultural factors. This study will discuss how the use and appropriation of technology through technical images are captured, allowing aesthetic results in photographs and how these images represent the daily lives of adolescents. Understanding this relationship supports numerous studies founded in the Humanities. This way, it was necessary to verify what guides the object to be studied, in this case, the photography and especially the implications present in the surroundings of visual perception. Considering the pinhole photography as a tool for creating, is generated the opportunity of questioning make with technique, with the same technology. From this, the main objective is to foster discussion about determinism of so called "technical images" as well as its placement in the media apparatus. It is estimated from this study highlight the socio-cultural dimensions of technology, questioning the homologous position of the photograph as a representation of reality, and providing to teenagers photographers a reflection on the technological processes as social mediators.